(untitled) (Swiss Medical Weekly, 2021)
The menstrual cycle increases insulin requirements in a subset of women with type 1 diabetes as a result of reduced insulin action through sexual hormones. If exposure to sexual hormones declines during the menopause, adaptions of insulin dosing may be required. However, there are no validated recommendations available on how to adapt insulin treatment in postmenopausal women with type 1 diabetes. The present study compared insulin dosing profiles of 630 premenopausal and 548 postmenopausal women, who had long-term type 1 diabetes and used continuous subcutaneous insulin infusion. Data were extracted from the German "Diabetes-Patienten- Verlaufsdokumentation". It was found that total daily insulin (p <0.0001), daily insulin per kilogram bodyweight (p <0.0001), total daily basal insulin (p <0.0001), daily basal insulin per kilogram bodyweight (p <0.0001) and estimated glomerular filtration rate (eGFR) (p <0.0001) were lower in postmenopausal women. Total daily bolus insulin, daily bolus insulin per kilogram, glycated haemoglobin A1, body mass index and the incidence of severe hypoglycaemic events were similar in both cohorts. Postmenopausal women with type 1 diabetes used lower insulin doses as compared with premenopausal women, whereas glycaemic control and body mass index were comparable. This observation might be explained by lower exposure to sexual hormones and lower eGFR, even though the contribution of other factors such as body composition and eating habits requires further investigation.